Evolutionarily Established Palmitoylation-Dependent Regulatory Mechanisms of the Vertebrate Glutamatergic Synapse and Diseases Caused by Their Disruption - Hayashi, Takashi (Frontiers in Molecular Neuroscience, 2021)
Glutamate is the major excitatory neurotransmitter in the vertebrate brain and various modifications have been established in the glutamatergic synapses. Generally, many neuronal receptors and ion channels are regulated by S-palmitoylation, a reversible post-translational protein modification. Genome sequence databases show the evolutionary acquisition and conservation concerning vertebrate-specific palmitoylation of synaptic proteins including glutamate receptors. Moreover, palmitoylation of some glutamate receptor-binding proteins is subsequently acquired only in some mammalian lineages. Recent progress in genome studies has revealed that some palmitoylation-catalyzing enzymes are the causative genes of neuropsychiatric disorders. In this review, I will summarize the evolutionary development of palmitoylation-dependent regulation of glutamatergic synapses and their dysfunctions which are caused by the disruption of palmitoylation mechanism.